1977
DOI: 10.1111/j.1365-2265.1977.tb02004.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stilboesterol Therapy on Thyrotrophin‐releasing Hormone (Trh) Responsiveness in Males

Abstract: TRH responsiveness was investigated in twenty-four males (aged 66-83 years) undergoing stilboesterol therapy for carcinoma of the prostrate. Twelve were taking 2-6 mg daily by mouth for periods of 5 days to 12 months (mean 5 months) (Group A) and the remainder were on daily i.v. doses of 250-500 mg for periods of 3-10 days (mean 8 days) (Group B). In the former group TRH responsiveness was enhanced compared to age matched controls. A contrary effect was observed in the latter group in that the group mean TRH r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This effect is presumably related to the estrogen therapy. It has been previously reported that exogenous estrogens may increase the TSH response to TRH in the male, although this is not a uniform observation and does not occur in normal females (1)(2)(3)(4)16). There is also no firm relationship between TSH secretion and endogenous estrogens.…”
Section: -mentioning
confidence: 68%
See 2 more Smart Citations
“…This effect is presumably related to the estrogen therapy. It has been previously reported that exogenous estrogens may increase the TSH response to TRH in the male, although this is not a uniform observation and does not occur in normal females (1)(2)(3)(4)16). There is also no firm relationship between TSH secretion and endogenous estrogens.…”
Section: -mentioning
confidence: 68%
“…This is supported by the fact that the administration of ethinyl estradiol to these subjects converted their TSH responses to the normal female pattern. Exogenous estrogen administered to normal males and to those with prostatic carcinoma may increase their TSH responses to TRH (1,16), although this has not been a uniform observation (4).…”
Section: -mentioning
confidence: 96%
See 1 more Smart Citation
“…The TRH double stimulation test, however, could not disclose any modulating properties of oestrogens on Prl and TSH secretion during the cycle. Only pharmacological doses of oestrogens may increase hypophyseal Prl and TSH secretion (Carlson et al 1973;Faglia et al 1973;Mortimer et al 1974;Ramey et al 1975;Reymond & LemarchandBéraud 1976;Smyth et al 1977).…”
Section: Discussionmentioning
confidence: 98%
“…It is known that TSH response to TRH is regulated also by hypothalamic dopamine (DA), which ex erts an inhibitory action on TSH secretion [1], Evidence suggests that estrogens exert a predominant anti-DA effect [6], whereas an opposite action of androgens has not been surely demonstrated. Thus, while changes in serum estrogen levels arc often accompanied by a concomitant variation in pituitary TSH responsiveness to TRH [5,15], conversely a fall in serum androgen levels, as recorded in the present study, does not induce this ef fect.…”
Section: Discussionmentioning
confidence: 57%